The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1093/scipol/scy048
|View full text |Cite
|
Sign up to set email alerts
|

Responsible research and innovation in Europe: A cross-country comparative analysis

Abstract: The objective of this article is to contribute to the emerging attempts to foster empirical, quantitative approaches to Responsible Research and Innovation (RRI), and to provide a low-resolution map of the European RRI landscape, which can serve as a vehicle for international learning. The article presents indicators of RRI aimed at characterising countries. It examines the empirical structure of the data collected in the ‘Monitoring the evolution and benefits of Responsible Research and Innovation’ (MoRRI) pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 41 publications
(32 reference statements)
1
16
0
1
Order By: Relevance
“…This work has however been recorded at the national level. Little is known about how the activity compares across institutes in different countries, with distinct traditions of public engagement in science [ 16 ] [ 17 ], scientific systems, and R&D resources [ 18 ], that allows for a broader understanding of this capacity building in contexts of internationally increasing public engagement demands [ 19 ] [ 20 ] [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This work has however been recorded at the national level. Little is known about how the activity compares across institutes in different countries, with distinct traditions of public engagement in science [ 16 ] [ 17 ], scientific systems, and R&D resources [ 18 ], that allows for a broader understanding of this capacity building in contexts of internationally increasing public engagement demands [ 19 ] [ 20 ] [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Yet, the question relating to how science communication varies across countries and global regions has received very little attention. The handful of cross-country comparisons point to some country variation in science communication [ 27 ] [ 16 ] [ 28 ] [ 25 ], but these variations are small among scientists. More recent research shows that this activity associates with the organisational contexts in which scientists work: our global survey of astronomers (N = 2,600) showed that those scientists working with more resources from their institutions were also more active communicators, regardless of the global region in which they worked [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since we based our framework on early RRI literature (published between 2011 and 2015), we compared our framework with RRI frameworks published since 2015 (Foley, Bernstein, and Wiek 2016;Jirotka et al 2016;Lubberink et al 2017b;Macnaghten, Owen, and Jackson 2016;Mejlgaard, Bloch, and Madsen 2018;Ribeiro, Smith, and Millar 2017;Silva et al 2018;Stahl and Coeckelbergh 2016;Stahl et al 2017;Tait 2017;Van de Poel et al 2017).…”
Section: Comparing the Rri Implementation Framework With Other Rri Frmentioning
confidence: 99%
“…Like our framework, most frameworks published since 2015 aimed to make RRI more concrete to support its implementation in practice (Foley, Bernstein, and Wiek 2016;Lubberink et al 2017b;Mejlgaard, Bloch, and Madsen 2018;Ribeiro, Smith, and Millar 2017;Silva et al 2018;Stahl et al 2017;Van de Poel et al 2017). Foley, Bernstein, and Wiek (2016) for example add the dimension 'coordination' to make more explicit how the other dimensions, especially engagement, should be performed, Ribeiro, Smith, and Millar (2017) While several of these frameworks emphasize that responsible processes do not guarantee responsible products (e.g.…”
Section: Comparing the Rri Implementation Framework With Other Rri Frmentioning
confidence: 99%
“…Authors emphasize importance of additional in depth analysis to acquire more representative measure of innovation performance. Mejlgaard et al (2019) Crişan et al (2018) focused their examination on the European Union least performing countries: Bulgaria and Romania. According to the SII data in the period from 2010 to 2016 EU innovation performance has increased but not all members participated equally.…”
Section: Literature Overviewmentioning
confidence: 99%